Proceedings of the 8th World Construction Symposium 2019
DOI: 10.31705/wcs.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

A review of smart technology usage in construction and demolition waste management

Abstract: The management of construction and demolition (C&D) waste, a major part of solid waste, is increasingly become a critical challenge in the quest of social, environmental, and economic sustainability. Innovative and smart technologies are emerging to provide inevitable benefits because of their capacity to enable digitisation, automation, and integration of Solid Waste Management (SWM) processes. Nevertheless, the application of such technologies in Construction and Demolition Waste Management (CDWM) has not ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It includes construction waste management, BIM, GIS, and optimization keywords. Lack of historical data, inaccuracy in estimation, inconsistencies in reported data, and lack of established platforms for promoting the circularity of recovered waste materials through reusing and recycling are among the issues hindering the application of advanced technology use in waste management [114]. Additionally, existing CDW management tools suffer from insufficient data quality, lack of interoperability with other software, and inability to integrate with the design process [107].…”
Section: Emerging Technologies In Waste Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes construction waste management, BIM, GIS, and optimization keywords. Lack of historical data, inaccuracy in estimation, inconsistencies in reported data, and lack of established platforms for promoting the circularity of recovered waste materials through reusing and recycling are among the issues hindering the application of advanced technology use in waste management [114]. Additionally, existing CDW management tools suffer from insufficient data quality, lack of interoperability with other software, and inability to integrate with the design process [107].…”
Section: Emerging Technologies In Waste Managementmentioning
confidence: 99%
“…Some academics have reported that the dearth of innovative technology in CDW management is impeding the development of effective management practices in the construction industry. Globally, information technologies are rapidly being used to improve the efficiency of CDW management and to mitigate the environmental and social consequences of waste disposal [114,115]. The application of emerging technologies and data analytics, such as BIM and big data, has been examined for CDW quantification, tracking, control, and management [107].…”
Section: Emerging Technologies In Waste Managementmentioning
confidence: 99%
“…Thus, providing reliable waste information is critical in WT. Intending to promote the WT practices in the C&D waste stream, Ratnasabapathy et al (2019b) have proposed that Blockchain (a decentralised and distributed data management and transaction technology) based platforms can improve operational efficiency, traceability, transparency and trust in WT processes while facilitating the sharing, reporting and auditing of waste materials without a trusted intermediary. They can also create wider circular business networks.…”
Section: Resultsmentioning
confidence: 99%
“…Construction and Demolition Waste Management (CDWM) includes several aspects, such as those social, environmental, economic, institutional, and political, by dealing with technology, engineering, management, legislation, and policies. According to Ratnasabapathy et al (2019), the blockchain technology can facilitate waste data management and trading of waste by improving the operational, connecting generators with waste consumers without an intermediary. Proper management of construction materials is mandatory for the safeguarding of the environment and also for the health of workers.…”
Section: System Implications and Impactmentioning
confidence: 99%